Urban Design and Multimodal Transportation: Using Urban Form and Accessibility Factors to Estimate Modal Shares and Energy Use from Transportation - Stojanovski, Todor (Proceedings from the Annual Transport Conference at Aalborg University, 2018)
A major urban challenge in European cities is the shift towards more energy efficient environmental friendly transportation modes (walking, cycling and public transportation). To make this possible there is a need to provide information about possibilities to use different modes of transportation in cities and energy use from transportation in buildings. This paper proposes, describes, tests and discusses a model to estimate modal shares of different transportation modes (walking, cycling, public transportation and private automobile) and calculate energy use from transportation based only urban form and accessibility factors. The aim is to visually inform actors and stakeholders such as real property developers, municipalities, public authorities, etc. about how well different buildings are integrated with walking, cycling, public transportation and private car, potential energy use and environmental impacts.